ECONOMIC GLOBALIZATION, ECONOMIC GROWTH, AND HUMAN CAPITAL : EMPIRICAL EVIDENCE USING THREE STAGE LEAST SQUARE IN INDONESIA - Huda, Qorinul; Istiana, Nofita (PATTIMURA UNIVERSITY, 2024)
The pace of globalization is increasing rapidly and dynamically as time goes by. Indonesia, located takes advantage of globalization to encourage economic growth. However, over the last decade, from 2000 to 2019, Indonesia's economic globalization index has tended to decline along with the increase in the global economic globalization index. Indonesia's economic growth has been relatively stagnant. Human capital, as the primary input in Indonesia's economic system, is suspected to be suboptimal. In the National Medium-Term Development Plan (RPJMN) for 2020-2024, economic growth and human capital are the main focus in achieving national prosperity. Human capital in this study uses health indicators as a proxy for assessing productivity and educational investment approaches. Data is transformed to meet the stationarity requirements of time series data. The study employs the Three Stage Least Square (3SLS) simultaneous equation method to examine total and direct effects. The estimation results show that changes in globalization growth are directly influenced by changes in economic growth, exchange rate growth, and inflation. Changes in economic growth are directly influenced by changes in exchange rate growth, globalization index growth, and inflation. Human capital is directly influenced by changes in globalization index growth, changes in economic growth, inflation, previous-year inflation, and changes in unemployment rates